The Effect of Eccentric vs. Traditional Resistance Exercise on Muscle Strength, Body Composition, and Functional Performance in Older Adults: A Systematic Review With Meta-Analysis - Klemen Čretnik; Jernej Pleša; Žiga Kozinc; Žiga Kozinc; Stefan Löfler; Nejc Šarabon; Nejc Šarabon; Nejc Šarabon; Nejc Šarabon (Frontiers Media S.A., 2022)
The effects of eccentric exercise (ECC) in older adults have received limited scientific attention, considering the ample evidence for its effectiveness in general and athletic populations. The purpose of this paper is to review the effects of ECC exercise modalities vs. traditional or concentric (CON) exercise on muscle strength, body composition and functional performance in older adults. Inclusion criteria regarding the age was >55 years. Three major scientific literature databases (PubMed, Scopus and Web of Science) were screened for trials comparing the effect of ECC and CON exercise programs, and 19 papers were included in the meta-analysis. ECC and CON training programs were typically matched by the duration of each session. The difference between ECC and CON was expressed as standardized mean difference (SMD). Regarding isometric knee strength, the pooled effect favored ECC (SMD = 0.50), but was not statistically significant (p = 0.160). ECC exercise elicited greater improvements in timed up and go test (SMD = −0.68; p = 0.004), 2-min sit-stand test (SMD = 0.53; p = 0.030) and 30-s sit-stand test (SMD = 0.81; p = 0.002), but not in 6-min walking test (SMD = 0.01; p = 0.960). The effects on body composition and muscle architecture were unclear (SMD = −1.44 to 1.95; p = 0.060-0.689). In conclusion, our literature review indicates that ECC exercise is superior to, or at least as good as CON exercise for preserving health and overall function in older adults.